Oil Price Shocks, Exchange Rate Fluctuations, Foreign Direct Investment Inflows, and Macroeconomic Stability: Evidence from Kazakhstan Using a Vector Autoregressive Approach - Turlybekova, Altynai; Sarsenova, Akmaral E.; Baineyeva, Parida; Aitymbetova, Ainura N.; Abdibekov, Saken Ualikhanovich; Tazhibayeva, Raikhan Musamatovna; Duisenbek, Daniyal (International Journal of Energy Economics and Policy, 2025)
This study investigates the interplay between oil price shocks, exchange rate movements, foreign direct investment (FDI) inflows, and gross domestic product (GDP) in Kazakhstan. Using quarterly data for 2010Q1-2024Q4, a Vector Autoregression (VAR) model is employed to capture short- and medium-term dynamics among these variables. Stationarity tests confirm that all series are integrated of order one, while lag selection criteria support a VAR(3) specification. The empirical results indicate that GDP remains largely self-driven in the short run, but its long-term variability is increasingly influenced by exchange rate fluctuations and oil prices. FDI inflows are initially persistent yet strongly shaped by oil market volatility, while the real effective exchange rate (REER) proves highly sensitive to external energy shocks. Oil prices, by contrast, remain mostly exogenous. These findings underscore Kazakhstan’s structural dependence on global oil markets and highlight the need for diversification, fiscal stabilization mechanisms, and improved exchange rate management to strengthen macroeconomic resilience.